2019
DOI: 10.6007/ijarbss/v9-i2/5666
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Internal Environmental Factors on Operational Excellence of Manufacturing Industry: A Pilot Study

Abstract: This paper examines internal environmental factors that influence the operational excellence of SMEs manufacturing sector in Malaysia. The objective of this paper is to measure the reliability and validity of internal environmental factors and its construct. A pilot study was conducted among 30 SMEs company in Terengganu which represented by the managerial level who are closely linked to the manufacturing operations. This study adopted a survey method by using simple random sampling method for the data collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Based on the theoretical understanding of excellence models, the theoretical foundation of EFQM is also studied under the theoretical domain of resource-based theory (Ruiz-Carrillo and Fernández-Ortiz, 2005). Different empirical findings on OE were conducted in the theoretical context of the resource-based view (Fok-Yew and Ahmad, 2014; Mohd Ali Smadi Ziad, 2018; Wahab et al , 2019). The applicability of the resource base view was also studied in the implementation of operational excellence methodologies like TQM, lean management and six sigma (Kiatcharoenpol et al , 2011; Kumar and Rodrigues, 2020; Tena et al , 2001).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Based on the theoretical understanding of excellence models, the theoretical foundation of EFQM is also studied under the theoretical domain of resource-based theory (Ruiz-Carrillo and Fernández-Ortiz, 2005). Different empirical findings on OE were conducted in the theoretical context of the resource-based view (Fok-Yew and Ahmad, 2014; Mohd Ali Smadi Ziad, 2018; Wahab et al , 2019). The applicability of the resource base view was also studied in the implementation of operational excellence methodologies like TQM, lean management and six sigma (Kiatcharoenpol et al , 2011; Kumar and Rodrigues, 2020; Tena et al , 2001).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Authors in [15] developed an OpEx framework. Authors in [16] showed the factors influencing OpEx of SMEs in Malaysia. Authors in [17] discussed the factors that can affect OpEx in the service sector and proposed a theoretical framework for this need.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%